2017
DOI: 10.1016/j.foodcont.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Innovative technologies to manage aflatoxins in foods and feeds and the profitability of application – A review

Abstract: Aflatoxins are mainly produced by certain strains of Aspergillus flavus, which are found in diverse agricultural crops. In many lower-income countries, aflatoxins pose serious public health issues since the occurrence of these toxins can be considerably common and even extreme. Aflatoxins can negatively affect health of livestock and poultry due to contaminated feeds. Additionally, they significantly limit the development of international trade as a result of strict regulation in high-value markets. Due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
189
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(197 citation statements)
references
References 132 publications
(160 reference statements)
1
189
1
6
Order By: Relevance
“…Kamber, Gülbaz, Aksu, and Doğan () evaluated the effects of three different ozone concentrations on the detoxification of dried red pepper samples, the results showed that a low dose of ozone application was more effective than higher dose application. It is generally considered that low concentration of ozone or short exposure time is more appropriate (Udomkun et al, ). Accordingly, the results demonstrated UV/O 3 were in compliance with the detoxifying effects of peanuts with ozone gas at concentration of 5 mg/L and detoxification time of 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Kamber, Gülbaz, Aksu, and Doğan () evaluated the effects of three different ozone concentrations on the detoxification of dried red pepper samples, the results showed that a low dose of ozone application was more effective than higher dose application. It is generally considered that low concentration of ozone or short exposure time is more appropriate (Udomkun et al, ). Accordingly, the results demonstrated UV/O 3 were in compliance with the detoxifying effects of peanuts with ozone gas at concentration of 5 mg/L and detoxification time of 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Gamma irradiation has been a promising intervention against mycotoxins and accepted by the food industry for treatment of dry food. Gamma irradiation produces high energy photons, which interact with microbial cells and induce DNA rupture (Udomkun et al, 2017). The chemical treatments using acetic acid, citric acid, lactic acid under simulated cooking (Aiko & Mehta, 2016) and bases such as NH 3 , Ca(OH) 2 , Na 2 CO 3 (Park, Lee, Price, & Pohland, 1988), oxidizing agents (for example, ozone), reducing agents (for example, NaHSO 3 ) are also used to reduce mycotoxins (Temba et al, 2016).…”
Section: Effect Of Plasma On Mycotoxinsmentioning
confidence: 99%
“…Management is a critical strategy for aflatoxin reduction. Aflatoxin management strategies include biological control [6,7], predictive modelling [8], innovative storage techniques [9], breeding efforts [10,11], aflatoxin reduction strategies [12] and detection [13]. However, detection plays a key role in aflatoxin management because many intervention methods hinge on the ability to monitor the production of the toxin [14,15].…”
Section: Introductionmentioning
confidence: 99%